Petrography and geochemistry of hydrothermally altered rocks from core well ASK-86, Hoffell - Fransie Williams 1970- (2021)
This study examined the chemical changes due to high-temperature alteration processes in the fossil geothermal system of Geitafell in east Iceland. Twenty-one samples from the ASK-86 core, drilled near the Hoffell farm, were analysed by ICP-OES to determine bulk rock composition and element mobility on a hand specimen scale. Further thirteen samples were analysed by SEM-EDS to reveal smaller scale element mobility. The most common rock type identified was basalt (57% of samples), followed by rhyolite (20%), then intermediate rocks (andesite 10%, trachy-andesite 5% and trachyte 5%). By SEM-EDS analysis, an intrusive rock with the uncommon composition of foidolite was also identified. Thin section analysis shows that all the primary minerals in these rocks have been replaced by secondary ones. Based on petrographic and SEM-EDS analyses, propylitisation, zeolitisation, silicification, chloritisation, and sulfidation were observed in all rock types, while albitisation was common in mafic rocks and K-feldspar deposition common in felsic rocks. The visible alteration minerals were similar for all rocks, indicating mobilisation of SiO2 (quartz veins, jasper, chalcedony), CaO (epidote, Ca-rich zeolites, calcite), FeO and MgO (chlorite, actinolite, clays), and S, Cu and FeO (pyrite and chalcopyrite). The composition of the core samples was compared to least altered rocks from Geitafell to establish the effect of high-temperature fluid migration on element mobility within different rock types. Mobilisation and redeposition of Ca, Fe, Mg and Na was observed in basalts, while intermediate rocks have a net gain in Ni and loss of Sr, and rhyolitic rocks lost Na and gained K and Rb. Some major elements, which are immobile on a hand specimen scale, show mobility on a micro scale (SEM-EDS). This micro scale element mobility is most noticeable for K. Brecciation resulted in the complete loss of alkalis, and a loss or gain in other elements to the extent that it was impossible to determine the original rock type of the breccia ...